Preparation and characterization of amino-functionalized Fe3O4/poly(maleic anhydride-co-acrylic acid) magnetic nanocomposite for removal of Cu(ll) and Ni(ll) ions - Shahri, Mahnaz Mahdavi (2013)
Toxic metal contamination in water systems is a serious problem threatening human health and environment. Hence, many researches have been carried to develop effective technique for the removal of metal ions from water. Adsorption is one of the methods use in this field due to its effectiveness and easy operation. Magnetite nanocomposites are exceptional nano-adsorbent materials that can be effective in heavy metal removal. In this work, a novel amino-functionalized Fe3O4/poly(maleic anhydride-co-acrylic acid) (MAH-co-AA) magnetic nanosized adsorbent with a core/shell structure was successfully synthesized by a dispersion polymerization route. Iron oxide nanoparticles were used as a core, and poly(MAH-co-AA) as a shell and followed by amino-functionalization using diethylenetriamine (DETA) via carbodiimide activation. The suitability of the magnetic nanocomposites for adsorption of Cu(II) and Ni(II) cations and its efficiency were investigated. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that the magnetic Fe3O4/poly(MAH-co-AA) nanocomposites were highly uniform in size and cubic shape with the average size about 17.06 nm. The infrared spectroscopy suggested the existence of core/shell type. X-ray diffraction confirmed magnetite cores and also indicated that the binding process did not change the phase of Fe3O4. Magnetic measurement by vibrational sample magnetometer (VSM) revealed the nanoparticles were superparamagnetic and the saturation magnetization was 83.6 and 46.6 emu g-1 for pure Fe3O4 and composite nanoparticles, respectively. Measurements by VSM also showed that the degree of saturation magnetization increased with increasing iron oxide concentration from 1% to 7 wt % of Fe3O4. The binding of DETA on the magnetic Fe3O4/poly(MAH-co-AA) nanocomposites was demonstrated by the analyses of fourier transform infrared (FTIR) spectroscopy and energy dispersive X-ray spectrometry (EDX) attached to the SEM. The DETA concentration for the amino-functionalization was fixed at 1.85 mol for 2 g Fe3O4/poly(MAH-co-AA). The amino-functionalized magnetic nano-adsorbent Fe3O4/poly(MAH-co-AA)–NHR shows a good capability for the rapid and efficient adsorption of metal cations from aqueous solutions via the chelation mechanism. The ability of Cu(II) and Ni(II) adsorption of these nanoparticles for removal from aqueous solutions was measured by inductively coupled plasma optical emission (ICP-OES). Various factors affecting the metal uptake behavior such as contact time, temperature, pH, amount of nano-adsorbent and initial concentration of metal ions were investigated. The adsorption capacity for metal ions was greatly influenced by pH. The optimum pH for maximum adsorption on the magnetic nano-adsorbent was observed to be 6.5 and 6.0 for Cu(II) and Ni(II) respectively. The kinetic data showed that the adsorption process followed the pseudo-second order kinetic model. The best interpretation for the equilibrium data was given by Langmuir isotherm and the maximum adsorption capacities was 55.2 and 43.6 mg g-1 for Cu(II) and Ni(II), respectively. Thermodynamic parameters such as the changes in free energy, enthalpy, and entropy of adsorption of copper and nickel were also evaluated. The negative values of the change in free energy indicate the feasibility and spontaneous nature of the process, and the positive values of the change in enthalpy indicate the endothermic nature of the adsorption process of Cu(II) and Ni(II). The metal-loaded Fe3O4/poly(MAH-co-AA)–NHR magnetic nano-adsorbent could be recovered readily from aqueous solution by magnetic separation and regenerated easily by acid treatment. Findings of the present work highlight the potential for using magnetic nanoparticles prepared as an effective nano-adsorbent with magnetic separability for the removal of heavy metal ions in water and wastewater treatment.